1956
DOI: 10.1113/jphysiol.1956.sp005513
|View full text |Cite
|
Sign up to set email alerts
|

Depressor reflexes from medullated and non‐medullated fibres in the rabbit's aortic nerve

Abstract: It is commonly believed that the reflex fall in systemic blood pressure which results from electrical stimulation of the aortic nerve is due to excitation of the barosensory fibres. However, Douglas & Schaumann (1956) concluded from their experiments on the reflex effects of electrical stimulation of the cat's aortic nerve that this nerve must contain additional depressor afferents smaller than any barosensory fibres that have been recognized in it. These small afferents are not easily characterized in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

1957
1957
2007
2007

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(31 citation statements)
references
References 14 publications
4
27
0
Order By: Relevance
“…They found that stimulation of the C fibres caused fused reflex muscular contractions at much lower frequencies than did excitation of the 8 fibres. The second finding is that of and Douglas, Ritchie & Schaumann (1956) who obtained analogous results with the non-medullated and medullated afferent fibres in the rabbit's vagus and aortic nerves. They found that the depressor reflexes associated with the C fibres were obtained at low frequencies of stimulation, often less than 1 shock/sec; such frequencies were much below those required to produce the depressor reflexes associated with the A fibres.…”
Section: Discussionsupporting
confidence: 53%
“…They found that stimulation of the C fibres caused fused reflex muscular contractions at much lower frequencies than did excitation of the 8 fibres. The second finding is that of and Douglas, Ritchie & Schaumann (1956) who obtained analogous results with the non-medullated and medullated afferent fibres in the rabbit's vagus and aortic nerves. They found that the depressor reflexes associated with the C fibres were obtained at low frequencies of stimulation, often less than 1 shock/sec; such frequencies were much below those required to produce the depressor reflexes associated with the A fibres.…”
Section: Discussionsupporting
confidence: 53%
“…In our experience, involving a total of some sixty experiments, there was never any increase in arterial pressure on aortic nerve stimulation, which agrees with the observations of Mott (1963) and Douglas et al (1956), and contrasts with the effects of sinus nerve stimulation which in the rabbit excites respiration and often increases arterial pressure. Electrical stimulation of the aortic nerve in the rabbit appears to be a convenient method of eliciting pure baroreceptor reflexes.…”
Section: Anaesthetics and Baroreceptor Pathways 549supporting
confidence: 63%
“…Douglas et al (1956) showed that in the rabbit electrical stimulation of the aortic nerve produced progressively greater reductions in arterial pressure as the applied voltage was increased. The series showed two phases, attributable to stimulation of low threshold A fibres, and of C fibres the threshold of which was higher than the maximal A fibre stimulus.…”
Section: Resuiltsmentioning
confidence: 99%
See 2 more Smart Citations